The effects of hypertensive disorders of pregnancy on fetal myocardial remodelling and cardiac function assessed by two-dimensional speckle tracking imaging - Yanhong Zhang; Lisi Zhang; Congxin Sun; Guihong Chen; Wei Zhao; Na Li; Jing Ma; Jianli Xue; Pin Wang; Wei Xiang; Shuping Ge; Yanju Wang (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective To assess the effects of hypertensive disorders of pregnancy on fetal myocardial remodeling and cardiac function applying two-dimensional speckle tracking techniques.Methods This is a case-control study with a 1:1 ratio, including fetuses with normal development and those exposed to hypertensive disorders of pregnancy. A total of 108 fetuses were included in the study, comprising 54 in the case group and 54 in the control group. A series of parameters, including ventricular size, spherical index, ejection fraction, myocardial strain, fractional change in ventricular area, and short axis shortening rate, were measured using Fetal HQ software with two-dimensional speckle tracking imaging. Statistical methods were employed to compare the case and control groups, with the aim of assessing the impact of hypertensive disorders of pregnancy on fetal myocardial remodeling and cardiac function.Results (1) The end-diastolic longitudinal diameter and area of the right ventricle in the HDP group were statistically significantly smaller than those in the control group (p < 0.05). However, no statistically significant differences were observed in the longitudinal and transverse diameters and areas of the four-chambered heart, as well as the longitudinal diameter and area of the left ventricle, when comparing the two groups (p > 0.05). (2) In terms of fetal cardiac morphology, the right ventricular segments 2–7 SI in the HDP group were observed to be smaller than those in the control group, with a statistically significant difference (p < 0.05). Conversely, the differences between the two groups in right ventricular segment 1, right ventricular segments 8–24 SI, left ventricular segments 24 SI and four-chambered cardiac GSI were not statistically significant (p > 0.05). (3) In terms of fetal ventricular systolic function, the HDP group exhibited lower left ventricular ejection fraction and cardiac output, right ventricular GLS, left and right ventricular FAC, left ventricular FS in segments 10–24, and right ventricular FS in segments 11–16 than the control group. These differences were statistically significant (p < 0.05). Furthermore, the left ventricular GLS, GCS, and right ventricular free wall St, left ventricular segments 1–9, and right ventricular segments 1–10 and 4-chamber GSI were observed to be lower than those of the control group. The GLS, GCS, and free wall St of the right ventricle, as well as the GLS, GCS, and free wall St of the left ventricle (segments 1–9) and the right ventricle (segments 1–10 and 12–24) were also evaluated.Conclusion Hypertensive disorders of pregnancy (HDP) have been demonstrated to affect fetal myocardial remodeling and contractile function, with a more pronounced impact observed on the right ventricle compared to the left ventricle. Two-dimensional speckle tracking technology offers the potential to provide more detailed information for the quantitative assessment of fetal size, morphology and cardiac function.